2022
DOI: 10.2174/1386207323999201230205435
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and Exosome in Retinal-related Diseases: Their Roles in the Pathogenesis and Diagnosis

Abstract: Abstract:: The precise and exquisite architecture of the retina is directly related to vision. Therefore, any mechanisms which are associated with disruption of retinal structure could affect on quality of vision. A large number studies indicated that several cellular and molecular processes involved in retina pathogenesis. Among different risk factors which are reported as important players in the retina diseases, deregulation of epigenetic contributors, have critical roles in the pathogenesis of these diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The released exosomes carry double-stranded DNA, mRNA, noncoding RNA (microRNA and lncRNA), and undigested or partially digested proteins out of the cell. This suggests that exosomes act as vital mediators during intercellular communication [ 32 , 33 ]. Exosomes perform important roles in both physiological and pathological processes in AMD [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The released exosomes carry double-stranded DNA, mRNA, noncoding RNA (microRNA and lncRNA), and undigested or partially digested proteins out of the cell. This suggests that exosomes act as vital mediators during intercellular communication [ 32 , 33 ]. Exosomes perform important roles in both physiological and pathological processes in AMD [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are non-coding RNAs with a length of 19–24 nucleotides that regulate gene expression of more than 30% of human genes following transcription. They pair to their target's untranslated 3′(3′-UTR) region of mRNAs, resulting in inhibition or degradation of the mRNAs 21 . Up or down-regulation or misplacement of miRNAs may play crucial roles in cancer development, tumor cell proliferation, migration, invasion, and chemical resistance 22 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Their advantage over stem cells has to do with their low immunogenicity and easier administration. EVs or exosomes (Exos, EVs with 30-200 nm diameter size) collected from mesenchymal stem cells (MSCs) have been applied to animal models of retinal and eye diseases including diabetic retinopathy (DR), glaucoma and agerelated macular degeneration (AMD) and proved effective mainly through their powerful anti-inflammatory effects [11][12][13][14][15]. One study of a rat model used neural progenitor cells (NPC)-Exos and reported an inhibition of the pro-inflammatory factors (including tumor necrosis factor-α/TNF-α, IL-1β and COX-2) [9], but only few studies explored the effect and mechanism of MSC-EVs on degenerated photoreceptors.…”
Section: Introductionmentioning
confidence: 99%